Words-Deeds Gap for the Purchase of Fairtrade Products: A Systematic Literature Review - Kossmann, Elena; Gomez-Suarez, Monica (Frontiers in Psychology, 2019)
Abstract Rationale: Nowadays ethical consumerism is part of the agenda of consumers, businesses and governments for its promise of a brighter future through the consumption of goods with added social or environmental value. Consumption of fair trade goods has been enjoying huge growth in the last few years as people are becoming more conscious of their consumption practices. Objective: In this piece of research we identify existing literature on the words-deeds gap for the purchase of fairly traded products. Moreover, we present and analyze the moderators to the ethical purchasing gap. Method: A collection of research articles was compiled using a key-word search in 3 databases: Scopus, SpringerLink and ScienceDirect. The research was carried out using various groups of keywords and completed using the following three criteria: articles published in English, between 2010 and 2018, in refereed journals. Further to the systematic literature review, all pertinent articles were imported into Atlas.ti for further thematic analysis. Results: 2,078 articles were identified from which 32 met the inclusion criteria. The content analysis resulted in the following themes: Values, Theory of Planned Behavior and Theory of Reasoned Action, Willingness-to-pay, Labels and Certification, Religion, Guilt, Dual Attitudes, Demographics Conclusion: Despite “moral” products tasting better and self-claims to this direction, there is still a gap between claimed and actual consumption. Implicit attitudes, an area currently underrepresented in FT research, could prove useful insights that may increase consumption of FT products.